Comparisons of Long-Term Survival and Safety of Haploidentical Hematopoietic Stem Cell Transplantation After CAR-T Cell Therapy or Chemotherapy in Pediatric Patients With First Relapse of B-Cell Acute Lymphoblastic Leukemia Based on MRD-Guided Treatment - Hu, Guanhua; Cheng, Yifei; Zuo, Yingxi; Chang, Yingjun; Suo, Pan; Jia, Yueping; Lu, Aidong; Wang, Yu; Jiao, Shunchang; Zhang, Longji; Sun, Yuqian; Yan, Chenhua; et al. (Frontiers in Immunology, 2022)
Measurable residual disease (MRD) positivity before haploidentical hematopoietic stem cell transplantation (haplo-HSCT) is an independent prognostic factor in determining outcomes in patients with B-cell acute lymphoblastic leukemia (ALL). In this study, we conducted a parallel comparison of the efficacy and safety in patients with suboptimal MRD response after reinduction who underwent haplo-HSCT after chimeric antigen receptor T-cell (CAR-T) therapy or chemotherapy. Forty B-cell ALL patients who relapsed after first-line chemotherapy and with an MRD ≥0.1% after reinduction were analyzed. The median pre-HSCT MRD in the CAR-T group (n = 26) was significantly lower than that in the chemotherapy group (n = 14) (0.009% vs. 0.3%, p = 0.006). The CAR-T group exhibited a trend toward improved 3-year leukemia-free survival and a significantly improved 3-year overall survival compared to the chemotherapy group [71.8% (95% confidence interval (CI): 53.9–89.6) vs. 44.4% (95% CI: 15.4–73.4), p = 0.19 and 84.6% (95% CI: 70.6–98.5) vs. 40.0% (95% CI: 12.7–67.2), p = 0.008; respectively]. Furthermore, no increased risk of graft-versus-host disease, treatment-related mortality, or infection was observed in the CAR-T group. Our study suggests that CAR-T therapy effectively eliminates pre-HSCT MRD, resulting in better survival in the context of haplo-HSCT.